Comorbidities in difficult asthma are independent risk factors for frequent exacerbations, poor control and diminished quality of life. Issue 8 (1st July 2016) - Tay, Tunn Ren; Radhakrishna, Naghmeh; Hore‐Lacy, Fiona; Smith, Catherine; Hoy, Ryan; Dabscheck, Eli; Hew, Mark
ABSTRACT: Background and objective: Little is known about how comorbidities affect difficult asthma patients across different domains of asthma outcomes. We hypothesized that comorbidities in difficult asthma significantly influence asthma outcomes. Methods: We analysed 90 consecutive patients who underwent systematic assessment at our hospital's difficult asthma clinic. Eight comorbidities were assessed in all patients. They were allergic rhinitis, chronic rhinosinusitis (CRS), gastroesophageal reflux disease, obesity, obstructive sleep apnoea, anxiety or depression, dysfunctional breathing (DB) and vocal cord dysfunction (VCD). Asthma outcomes examined were exacerbation frequency (≥3/year vs <3/year), asthma control using the Asthma Control Test (ACT) and quality of life using the Asthma Quality of Life Questionnaire (AQLQ). Multivariate logistic regression was performed for dichotomous outcomes and linear regression for continuous outcomes. Analyses were adjusted for lung function and absolute blood eosinophils. Results: Increasing BMI was an independent risk factor for exacerbations (OR: 1.1, 95% CI: 1–1.1, P  = 0.042), lower ACT score ( β coefficient: −0.25, 95% CI: −0.37 to −0.12, P  < 0.001) and poorer AQLQ ( β coefficient: −0.05, 95% CI: −0.09 to −0.02, P  = 0.006). DB predicted lower ACT ( β coefficient: −2.85, 95% CI: −5 to −0.7, P  = 0.01) and AQLQ scores ( β coefficient: −0.73, 95% CI: −1.34 to −0.12, P  = 0.02). Patients with CRS had more exacerbations (OR: 4, 95% CI: 1.5–10.9, P  = 0.006). Patients with VCD had lower AQLQ scores ( β coefficient: −0.78, 95% CI: −1.38 to −0.18, P  = 0.012). Conclusion: Comorbidities independently impact a broad spectrum of outcomes in difficult asthma. Systematic evaluation of these conditions is essential in difficult asthma. Abstract : This study examined comorbidities in a consecutive cohort of difficult asthma patients. Increasing BMI, chronic rhinosinusitis, dysfunctional breathing and vocal cord dysfunction were independent risk factors for a broad spectrum of asthma outcomes. Identification and treatment of these comorbidities are essential in management of patients with difficult asthma.